PENGARUH WAKTU REAKSI DAN WAKTU TINGGAL STABILISASI PADA SEQUENCING BATCH REACTOR AEROB DENGAN PENAMBAHAN KARBON AKTIF TERHADAP PENURUNAN CHEMICAL OXYGEN DEMAND - Hadiwododo, Mochtar; Junaidi, Junaidi (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2007)
Sequencing  Batch  Reactor  (SBR)  process  represent  biological  wastewater  treatment  with aerobic process  used  occasionally  to  eliminate  dissolve  organic  materials  constructively microorganism especially  bacterium  in  course  of  organic  degradation.  Sequencing  Batch Reactor(SBR )has five phase in its cycle, namely fill, react, setlle, draw and iddle phase. In this study iddle phase was changed into stabilization phased where microorganism oxydize organic matter  as  stored  materials  in  cell  under certain  aeration  period  of  time.The  objectives  of  this research are to know influence of time react and time stabilisation with added of Granular Active Carbon  (GAC)    to  COD  removal.  In  research  was used  reactor  from  plastic  material  with diameter  25  cm  and  high  is  25  cm,  volume  of wastewater  in  reactor  is  5  liter  and  volume  of sludge is 35% from volume of wastewater that 1,75 liter. Waste that used was artificial waste glucose soluble with 1032.5 mg/l concentration of COD. As independent variable are react time: (0,5 ; 1; 1,5 ; 2 hours) and stabilitation time (3; 4; 5; 6 hours), if dependent  variable are removal of  carbon.  Application  of  Granular  Active  Carbon  (GAC)  as absorbent,  combined  with suspended  system  of  SBR,  is  expected  to  be  able  to  remove  COD better.  As  the  result  this research  shows  that the finest of  carbon removal   is occurred  in time react 1  hours, andtime stabilitation 6 hours  is 97.23%. COD removal with GAC better than that without GAC.